2014
DOI: 10.1063/1.4865928
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the internal electric field distribution of alternating current driven organic light-emitting devices for a reduced operating voltage

Abstract: The influence of the thickness of the insulating layer and the intrinsic organic layer on the driving voltage of p-i-n based alternating current driven organic light-emitting devices (AC-OLEDs) is investigated. A three-capacitor model is employed to predict the basic behavior of the devices, and good agreement with the experimental values is found. The proposed charge regeneration mechanism based on Zener tunneling is studied in terms of field strength across the intrinsic organic layers. A remarkable consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…For double‐insulated AC‐driven OLEDs, there are two important issues affecting device operation: the generation of electrons and holes and the choice of dielectric layer. Several approaches have been proposed for the generation of charge carriers, such as employing nanoparticle layers (NPLs), introducing colloidal quantum dots (QDs), and doping charge‐transport layers (p‐ and n‐doping) . Lee and co‐workers first utilized NPLs as bipolar charge‐generation layers in double‐insulation AC‐driven OLEDs and observed uniform surface emission.…”
Section: The Best‐performing Ac‐driven Oleds Based On Different Strucmentioning
confidence: 99%
See 2 more Smart Citations
“…For double‐insulated AC‐driven OLEDs, there are two important issues affecting device operation: the generation of electrons and holes and the choice of dielectric layer. Several approaches have been proposed for the generation of charge carriers, such as employing nanoparticle layers (NPLs), introducing colloidal quantum dots (QDs), and doping charge‐transport layers (p‐ and n‐doping) . Lee and co‐workers first utilized NPLs as bipolar charge‐generation layers in double‐insulation AC‐driven OLEDs and observed uniform surface emission.…”
Section: The Best‐performing Ac‐driven Oleds Based On Different Strucmentioning
confidence: 99%
“…The luminance is higher at higher doping concentration with increasing voltage, which again confirms the operational mechanism. The influence of the insulator and organic‐layer thickness, which is related to the internal electric field, on the device performance of AC‐driven OLEDs with p‐ and n‐doped charge‐transport layers was systematically investigated by Fröbel et al, as shown in Figure a . Reducing the insulating layer thickness to below 120 nm can lead to further improvements in the driving voltage and even in the efficiency (Figure b).…”
Section: The Best‐performing Ac‐driven Oleds Based On Different Strucmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the frequent overturning of the applied electric field, the charges accumulation can be effectively avoided, which may improve the power efficiency and operational lifetime. The insulating dielectric can effectively eradicate the direct current injection and preventing electrochemical reactions between the emissive layer and the electrodes, as well as preventing the deterioration of the emissive layer by the external moisture and oxygen in the atmosphere . Given these advantages, it is facile for the AC‐driven EL devices to be integrated for use with the AC power sources with 110/220 V at 50/60 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, reports on AC driven OLEDs demonstrate relatively modest efficiencies, especially for capacitively coupled AC-OLEDs, operating in a fully insulated mode, i.e. without charge injection from external electrodes [5][6][7][8]. For this capacitively coupled configuration, the most promising approach in terms of brightness and efficiency is a p-i-n based architecture in which a single emissive unit is surrounded by doped hole and electron transport layers and by a pair of insulating layers; the whole stack is then sandwiched between two electrodes [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%